Offspring of Obese Dams Exhibit Sex-Differences in Pancreatic Heparan Sulfate Glycosaminoglycans and Islet Insulin Secretion - Casasnovas, Jose; Damron, Christopher Luke; Jarrell, James; Orr, Kara S.; Bone, Robert N.; Archer-Hartmann, Stephanie; Azadi, Parastoo; Kua, Kok Lim (Frontiers in Endocrinology, 2021)
Offspring of obese mothers suffer higher risks of type 2 diabetes due to increased adiposity and decreased β cell function. To date, the sex-differences in offspring islet insulin secretion during early life has not been evaluated extensively, particularly prior to weaning at postnatal day 21 (P21). To determine the role of maternal obesity on offspring islet insulin secretion, C57Bl/6J female dams were fed chow or western diet from 4 weeks prior to mating to induce maternal obesity. First, offspring of chow-fed and obese dams were evaluated on postnatal day 21 (P21) prior to weaning for body composition, glucose and insulin tolerance, and islet phasic insulin-secretion. Compared to same-sex controls, both male and female P21 offspring born to obese dams (MatOb) had higher body adiposity and exhibited sex-specific differences in glucose tolerance and insulin secretion. The male MatOb offspring developed the highest extent of glucose intolerance and lowest glucose-induced insulin secretion. In contrast, P21 female offspring of obese dams had unimpaired insulin secretion. Using SAX-HPLC, we found that male MatOb had a decrease in pancreatic heparan sulfate glycosaminoglycan, which is a macromolecule critical for islet health. Notably, 8-weeks-old offspring of obese dams continued to exhibit a similar pattern of sex-differences in glucose intolerance and decreased islet insulin secretion. Overall, our study suggests that maternal obesity induces sex-specific changes to pancreatic HSG in offspring and a lasting effect on offspring insulin secretion, leading to the sex-differences in glucose intolerance.